Comparative Performance of Screening Instruments for Obstructive Sleep Apnea in Morbidly Obese Patients Referred to a Sleep Laboratory: a Prospective Cross-Sectional Study - Duarte, R (2021)
Purpose: Obstructive sleep apnea (OSA) is very common occurrence among morbidly obese patients. Our main objectives were to validate the No-Apnea, a 2-item screening tool, in morbidly obese patients and compare its performance with three other instruments: STOP-Bang questionnaire, NoSAS score, and Epworth Sleepiness Scale (ESS). Methods: A cross-sectional analysis of morbidly obese patients (body mass index [BMI] ≥ 35.0 kg/m2) grouped into two independent samples: bariatric surgery patients (BS) and non-bariatric surgery patients (NBS). All patients underwent overnight polysomnography. Discriminatory ability was assessed by area under the curve (AUC). OSA severity was defined by apnea/hypopnea index cut-off points: ≥ 5.0/h (OSA≥5), ≥ 15.0/h (OSA≥15), and ≥ 30.0/h (OSA≥30). Results: A total of 1017 subjects (40.4% in BS cohort and 59.6% in NBS cohort) were evaluated. In the BS cohort, No-Apnea had similar discrimination to STOP-Bang and NoSAS for predicting OSA≥5 (p = 0.979 and p = 0.358, respectively), OSA≥15 (p = 0.158 and p = 0.399, respectively), and OSA≥30 (p = 0.388 and p = 0.903, respectively). In the NBS cohort, No-Apnea had similar discrimination to STOP-Bang and NoSAS for predicting OSA≥5 (p = 0.528 and p = 0.428, respectively), OSA≥15 (p = 0.825 and p = 0.108, respectively), and OSA≥30 (p = 0.458 and p = 0.186, respectively). Moreover, No-Apnea performed significantly better than ESS in both BS and NBS cohorts (p < 0.001). Conclusions: No-Apnea is a useful and practical tool for screening of OSA in morbidly obese patients, with non-inferior performance to STOP-Bang questionnaire and NoSAS score.